A preliminary study of the dental implant therapy—initial osteogenesis of Human Mesenchymal Stem (HMS0014) cells on titanium discs with different surface modifications - IWAI, Yasutomo; MIKAMI, Yutaka; KUMABE, Shunji; MATSUDA, Yoshifumi; NAKATSUKA, Michiko (Okajimas Folia Anatomica Japonica, 2012)
HMS0014 cells were GBR-engineered to proliferate and differentiate into mature osteoblast(Ob)-like cells, which initiated hard tissue matrix deposition in both monolayer and PuraMatrix 3-D cultures. Subsequently, the osteogenesis initiated with attachment/adhesion of HMS0014 cells on either Titanium (Ti) or Ti alloy discs modified with osteoconductive/ osteoinductive surface textures/substrates (e.g., Disc-AO, Disc-HA, Disc-SPI) was histologically assessed. The results obtained were as follows: 1) The HMS0014 cells actively proliferated and differentiated into mature Obs to initiate mineralisation of the ECM since day 1 in both monolayer and 3-D cultures; mineralization was prominently progressed between day 7 and day 14 of cultures. 2) The SEM of 60-minute(min)s specimens demonstrated a loose distribution of proliferating spherical-to-polygonal (10 to 40 μm in diameter, avg.) cells with a bulging cell body sending out many minute filopodia and some lamellipodia to attach with the substrate in the concavities. 3) In the 180-min specimens, the cultured HMS0014 cells actively proliferated and spread into flat, large polygonal cells with prominent lamellipodia and dendritic filopodia (30 μm × 90 μm to 100 μm × 200 μm, approx.) to employ cell-to-substrate and intercellular attachments. 4) On the other hand, the present immunohistochemistry of the attached HMS0014 cells demonstrated the co-expression of F-actin (actin filaments of the cytoskeleton) and CD51 (αV integrin) in both the 60-min and 180-min specimens. We concluded that the present GBR method enhanced HMS0014 cells to initiate an osteogenesis process with a direct bone-to-substratum contact on Ti discs which were subject to different surface modifications.